2020
DOI: 10.1111/jcmm.15090
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signalling mediates drug resistance through targeting TAP1 in hepatocellular carcinoma

Abstract: Multidrug resistance is one of the reasons for low survival of advanced hepatocellular carcinoma (HCC). Our previous studies indicate that the hedgehog signalling is involved in hepatic carcinogenesis, metastasis and chemo-resistance. The present study aims to uncover molecular mechanisms underlying hepatoma chemo-resistance. TAP1 and GLI1/2 gene expression was assessed in both poorly differentiated hepatoma cells and HCC specimens. Potential GLI-binding site in the TAP1 promoter sequence was validated by mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…The authors could reverse resistance in the multiple drug-resistant HL-60 AML cell line using the SMO inhibitor NVP-LDE225, resulting in decreased protein expression of MRP1, which is a membrane drug transporter protein responsible for drug resistance and a poor prognosis in AML patients [ 35 ]. Furthermore, activated GLI signaling results in the upregulation of several drug transporters, including the ABC transporters ABCB1 , ABCB2 , and ABCG2 , DNA repair mechanisms, and drug-modifying enzymes of the UDP glucuronosyltransferase ( UGT1A ) family [ 22 , 36 , 37 , 38 ]. However, while the role of GLI signaling in drug resistance is well established, the involvement of GLI3 gene expression in the development of chemotherapy resistance has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The authors could reverse resistance in the multiple drug-resistant HL-60 AML cell line using the SMO inhibitor NVP-LDE225, resulting in decreased protein expression of MRP1, which is a membrane drug transporter protein responsible for drug resistance and a poor prognosis in AML patients [ 35 ]. Furthermore, activated GLI signaling results in the upregulation of several drug transporters, including the ABC transporters ABCB1 , ABCB2 , and ABCG2 , DNA repair mechanisms, and drug-modifying enzymes of the UDP glucuronosyltransferase ( UGT1A ) family [ 22 , 36 , 37 , 38 ]. However, while the role of GLI signaling in drug resistance is well established, the involvement of GLI3 gene expression in the development of chemotherapy resistance has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be explained by two reasons: (i) polymorphism of ABCB1 and/or ABCG2 determined the clinical response to sorafenib in patients with HCC [ 98 ]; and (ii) expression of the ABC transporters was associated with the differentiation degree of the HCC. ABCB1 and ABCG2 were mainly expressed in well-differentiated hepatoma cells, whereas poorly differentiated hepatoma cells expressed ABCC1 and ABCB2 (TAP1), accompanied by aberrant activation of the Hh signaling [ 17 ]. We have demonstrated that Hh transcription factors GLI1/2 were able to bind to the consensus sequence in the promoter of ABCC1 or ABCB2 to facilitate resistance to sorafenib, doxorubicin and cisplatin in poorly differentiated hepatoma cells.…”
Section: Hh Signaling In Drug Resistancementioning
confidence: 99%
“…We have demonstrated that Hh transcription factors GLI1/2 were able to bind to the consensus sequence in the promoter of ABCC1 or ABCB2 to facilitate resistance to sorafenib, doxorubicin and cisplatin in poorly differentiated hepatoma cells. Suppression of GLI1/2 by RNA interference approaches or GANT61, a GLI inhibitor, resulted in a decrease in expression of ABCC1 or ABCB2, and partially restored the chemosensitivity in these poorly differentiated hepatoma cells [ 16 , 17 ]. Moreover, ATO, another GLI1 inhibitor, improved the survival of a spontaneous mouse model of medulloblastoma with activated Hh pathway signaling [ 99 ].…”
Section: Hh Signaling In Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Most HCC patients lose the opportunity to have surgery when they are diagnosed and are mainly treated by trans-arterial chemoembolization (TACE), radiofrequency ablation, cryoablation, molecular targeted therapies, and other adjuvant treatments. However, these therapies have not signi cantly improved the 5-year survival rate of patients with HCCs [3] . Hence, actively searching for molecular markers and therapeutic targets for predicting the prognosis of patients with primary HCC is important for improving prognosis.…”
Section: Introductionmentioning
confidence: 99%